Heat Inleak along the Neck of Liquid Nitrogen Containers - Shaari, Abdul Halim (1985)
Measurements have been made of the temperature profile along the stainless steel neck of a 25 litre commercial dewar for the storage of liquid nitrogen. The temperature profile of the boundary layer of the effluent gas was also measured. The major heat inleak into the liquid nitrogen bath is due to the sold heat conduction down the neck wall and to the vapour recirculation process. These two sources contributed about 80% of the total heat inleak. The solid heat conduction was due to the fact that the neck was short and as such the refrigerative value of the cold effluent gas was not fully utilised. The vapour recirculation process is due to the reverse mass flux of the warmer gas into the bath.